"Not so globalised": contrasting media discourses on education and competitiveness in four countries. Issue 1 (7th January 2019) - Davis, Edward Rock; Wilson, Rachel
Abstract : Purpose: This paper aims to analyse contrasting discourses on education and competitiveness from four countries to show the different national values that are a key driver in economic development. Design/methodology/approach: The paper uses content analysis to compare and contrast the newspaper discourse surrounding the OECD Program for International Student Assessment (PISA) in four countries with above OECD average performance: Japan and South Korea (improving performance) and Australia and Finland (declining performance). PISA has attracted much government and public attention because it reflects education and the economic value of that education. Findings: There are key contrasts in the discourses of the four countries. Despite shifts to globalised perspectives on education, strong national and cultural differences remain. Educational competitiveness and economic competitiveness are strong discourses in Japan and South Korea, while in Australia and Finland, the focus is on educational competitiveness. The media in Finland has few references to economic competitiveness and it does not feature in Australia. The discourse themes on PISA from 2001 to 2015 are presented with trends in educational attainment and shifting national perspectives on education. Research limitations/implications: Analysis is limited to the top two circulation newspapers in English language in each country over 2001 to 2015. These newspapers in Finland, Japan and South Korea include translated content from local language papers. Originality/value: The paper provides longitudinal perspectives to understand the contrasting societal values placed on education and how these relate to perspectives on competitiveness. This media evidence on national discourses can inform education policy orientations in the four countries examined.